EARNING MANAGEMENT AND PROFITABILITY OF LISTED INSURANCE COMPANIES IN NIGERIA: THE MODERATING EFFECT OF ACCOUNTING ETHICS (Journal of Global Accounting, 2025)
This study examined the moderating effects of accounting ethics on the relationship between earning management and profitability of listed insurance firms in Nigeria. The study employed non-survey research design, using a sample size of eighteen (18) companies from a total population of twenty-eighty (28) listed insurance companies on the Nigerian Exchange Group (NGX) with data extracted from the annual reports and accounts of the sampled companies for a period of twelve years from 2012 to 2023. Data was analyzed using descriptive statistics to provide a summary for the variables and correlation analysis carried out using the correlation matrix technique. The analyses were done using STATA software version 14.2. The study found out that Accrual Earnings Mechanism (AEM) does not influence profitability but Real Earnings Mechanism (AEM) does. More so, accounting ethics does not affect profitability of the sampled companies in Nigeria. On the moderating effect of accounting ethics on the relationship between earnings management and profitability, it was found out that accounting ethics moderate the relationship between earnings management (using AEM) and profitability but when the earnings management was proxy with Real Earnings Mechanism (AEM), accounting ethics does not moderate the relationship between Real Earnings Mechanism (AEM) and profitability of listed insurance companies in Nigeria. Thus, this study recommends that the managers of the sampled companies in Nigeria should management should strengthen ethical guidelines and practices related to the use of AEM. This includes ensuring that accrual accounting methods are applied transparently and responsibly, as ethical practices can enhance the trustworthiness of financial reports and positively influence profitability. Also, management should focus on optimizing operational efficiencies and cash flow generation through REM. Strategies could include improving production processes, enhancing service delivery, and managing costs effectively
Keywords: Accounting Ethics; Earnings Management; Insurance Companies; Profitability